SISTEM PENGATURAN MOTOR DC MENGGUNAKAN PROPOTIONAL IINTEGRAL DEREVATIVE (PID) KONTROLER - Nur Salim (Universitas Nusa Cendana, 2012)
This research aims to control the DC motor rotation using the control system using PID (Proportional Integral Derivative). To see the performance of PID controller, it will be compared to a DC motor using PI controller (Proportional Integral)). From the results of experiments that have been done indicate that the DC motor using PID controller when starting without load takes about 0.066 seconds. While the DC motor using PI controller takes about 2.345 seconds. At the time of granting the load, the DC motor using PID controller requires recovery time to reach the setpoint was 0.034 seconds. While for DC motor using PI controller requires recovery time to reach the setpoint is 0.411 seconds.